Reclaiming Malcolm X: Epideictic Discourse and African-American Rhetoric. Issue 2 (3rd April 2021) - Rodriguez, Danny
ABSTRACT: This essay examines the epideictic rhetoric of Nuri Muhammad, a Nation of Islam student minister, at a Malcolm X Festival in 2018. Nuri's rhetorical performance demonstrates how he uses the memory of Malcolm X to create a collective epideictic experience with his audience. Using Malcolm X's "The Ballot or the Bullet" as a foundation, Nuri praises virtues and condemns vices that support the community's conception and preservation of Malcolm X, positioning the audience as judge rather than spectator. This performance illustrates how everyday cultural practices may deviate from our understanding of rhetoric while augmenting our research practices and goals.